Influence Price Discount and Shopping Lifestyle Against Impulse Buying - Huljannah, Mifta; Atridayansyah, Reza; Eryanto, Sapta (Journal of Islamic Economic Scholar, 2020)
Along with the development of the current era of globalization, companies and individuals have to work hard to fulfill their business continuity. Human needs that are increasing from time to time make it important to make decisions in meeting daily needs so that they are not easily tempted by new items that are not in accordance with their priorities. This study aims to determine, (1) the simultaneous influence between price discontent and shopping lifestyle on impulse buying, (2) partial effect between price discontent on impulse buying, (3) partially influence between shopping lifestyle on impulse buying. This research uses explanatory research with a quantitative approach. The sample used in this study amounted to 55 respondents who were consumers in the AII Collection in Bandung. The data collection method used in this study was a questionnaire. Data analysis using SEM-PLS with SmartPLS analysis tool is used as data processing. The results of this study indicate that (1) the price discont variable and shopping lifestyle simultaneously have a significant effect on impulse buying, (2) the price discont variable partially has a significant effect on impulse buying, (3) the shopping lifestyle variable partially has a significant effect on impulse buying.Keywords: Price discont, shopping lifestyle, impulse buying